p38β Mitogen-Activated Protein Kinase Modulates Its Own Basal Activity by Autophosphorylation of the Activating Residue Thr180 and the Inhibitory Residues Thr241 and Ser261 - Beenstock, Jonah (Mol Cell Biol, 2016)
Many enzymes are self-regulated and can either inhibit or enhance their own catalytic activity. Enzymes that do both are extremely rare. Many protein kinases autoactivate by autophosphorylating specific sites at their activation loop and are inactivated by phosphatases. Although mitogen-activated protein kinases (MAPKs) are usually activated by dual phosphorylation catalyzed by MAPK kinases (MAPKKs), the MAPK p38β is exceptional and is capable of self-activation by cis autophosphorylation of its activation loop residue T180. We discovered that p38β also autophosphorylates in trans two previously unknown sites residing within a MAPK-specific structural element known as the MAPK insert: T241 and S261. Whereas phosphorylation of T180 evokes catalytic activity, phosphorylation of S261 reduces the activity of T180-phosphorylated p38β, and phosphorylation of T241 reduces its autophosphorylation in trans. Both phosphorylations do not affect the activity of dually phosphorylated p38β. T241 of p38β is found phosphorylated in vivo in bone and muscle tissues. In myogenic cell lines, phosphorylation of p38β residue T241 is correlated with differentiation to myotubes. T241 and S261 are also autophosphorylated in intrinsically active variants of p38α, but in this protein, they probably play a different role. We conclude that p38β is an unusual enzyme that automodulates its basal, MAPKK-independent activity by several autophosphorylation events, which enhance and suppress its catalytic activity.